2022
DOI: 10.3389/fpubh.2022.1036299
|View full text |Cite
|
Sign up to set email alerts
|

The current status and factors related to the preparation of home first-aid kits in China

Abstract: BackgroundHome first-aid kits can play an important role when residents are injured, suddenly become seriously ill or suffer from disasters.PurposeTo explore the home first-aid kit preparedness of Chinese residents and the relationship between demographic sociological characteristics, self-efficacy, Big Five personality, health literacy and home first-aid kit preparation behavior.MethodsA cross-sectional study was conducted. Information was collected through a self-designed questionnaire consisting of sociolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Respondents with higher per capita household income were more likely to have a home first-aid kit. Similarly, a previous study has found that monthly household income was a factor affecting the behavior of residents in preparing emergency supplies [ 3 ]. The higher the monthly household income, the more conscious residents were regarding protecting their lives and property.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Respondents with higher per capita household income were more likely to have a home first-aid kit. Similarly, a previous study has found that monthly household income was a factor affecting the behavior of residents in preparing emergency supplies [ 3 ]. The higher the monthly household income, the more conscious residents were regarding protecting their lives and property.…”
Section: Discussionmentioning
confidence: 95%
“…The home first-aid kit is a comprehensive first-aid kit for accidents, such as knife wounds or earthquakes. They guarantee the safety of residents and play an important role when family members are injured [ 3 ]. In recent years, living standards have improved, and health awareness has been promoted.…”
Section: Introductionmentioning
confidence: 99%
“…The home rst-aid kit is a comprehensive rst-aid kit for accidents, such as knife wounds or earthquakes. They guarantee the safety of residents and play an important role when family members are injured [3]. In recent years, living standards have improved, and health awareness has been promoted.…”
Section: Introductionmentioning
confidence: 99%